DILEMMA PERILAKU KONSUMTIF DALAM PERANNYA MEMBANGUN BISNIS RITEL MODERN DI INDONESIA - Oktafalia Marisa (Business Management Journal, 2017)
Discount promotion in the retail industry has great charm to consumers. We can find this program in every single modern retail industry. In the past, big sale program or discount promotion could only be found find in midyear term or at the end of the year. Nowadays, the discount promotion is offered in each month. It’s a unique strategy for modern retail. Matahari dept. Store, as an example, has decided to use this strategy the results is the significant raise of their income. This offer is based on research about the habit of our Indonesian society in general. It’s called consumptive behavior. Although in basic theory it’s a well-known fact that becoming a consumptive person is not an option for in this society; in reality, the behavior saved a retail industry.Key Words- Economic Policy, Minimum Wage, Income.